2016
DOI: 10.1016/j.gene.2016.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A1: Structure, function and gene polymorphism

Abstract: Inducible expression of serum amyloid A (SAA) is a hallmark of the acute-phase response, which is a conserved reaction of vertebrates to environmental challenges such as tissue injury, infection and surgery. Human SAA1 is encoded by one of the four SAA genes and is the best-characterized SAA protein. Initially known as a major precursor of amyloid A (AA), SAA1 has been found to play an important role in lipid metabolism and contributes to bacterial clearance, the regulation of inflammation and tumor pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 122 publications
(177 reference statements)
1
137
1
3
Order By: Relevance
“…Early after induction of inflammation, IL6 is elevated and is required for efficient stimulation of epithelial cell proliferation after intestinal injury within a mouse model [44]. SAA1 is highly conserved and found to play a role in lipid metabolism as well as bacterial clearance and has a possible role in regulation of inflammation by extending the lifespan of neutrophils and activating proinflammatory cytokines (IL6, IL8, IL1beta, CXCL1, CXCL2) through several receptors including TLR2 and TLR4 [45]. …”
Section: Discussionmentioning
confidence: 99%
“…Early after induction of inflammation, IL6 is elevated and is required for efficient stimulation of epithelial cell proliferation after intestinal injury within a mouse model [44]. SAA1 is highly conserved and found to play a role in lipid metabolism as well as bacterial clearance and has a possible role in regulation of inflammation by extending the lifespan of neutrophils and activating proinflammatory cytokines (IL6, IL8, IL1beta, CXCL1, CXCL2) through several receptors including TLR2 and TLR4 [45]. …”
Section: Discussionmentioning
confidence: 99%
“…wileyonlinelibrary.com/journal/pro predictive of inflammatory processes, which could be regulated by IL-1, IL-6, TNF-, and glucocorticoids. 10 However, few studies have identified SAA as a biomarker in lung cancer patients. In the present prospective study, patients with locally advanced NSCLC were treated with thoracic radiotherapy, their peripheral blood samples were collected at different time-points, and their SAA levels were tested;…”
Section: 2 Amentioning
confidence: 99%
“…It is known that molecules, such as tumor necrosis factor‐α (TNF‐α), transforming growth factor‐β1, interleukin‐1 (IL‐1), interleukin‐6 (IL‐6), and interferon‐α, and changes in their gene expression are involved in the initiation and development of RP . Serum amylase A (SAA), an acute phase response protein, has been reported to be predictive of inflammatory processes, which could be regulated by IL‐1, IL‐6, TNF‐α, and glucocorticoids . However, few studies have identified SAA as a biomarker in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…10 The SAA gene family has 4 members. SAAs can be divided into 2 subgroups, comprising acute-phase SAA1 and SAA2 associated with HDL and inflammation in the first subgroup 11 and SAA4 in the second subgroup. SAA3 is expressed in mice but not in humans.…”
Section: Introductionmentioning
confidence: 99%